The effects of suspended sediment on brown trout ( Salmo trutta ) feeding and respiration after macrophyte control - MJC Greer; SK Crow; AS Hicks; GP Closs (New Zealand Journal of Marine and Freshwater Research, 2015)
Sediment resuspension during and after mechanical excavation of macrophytes may have a significant impact on resident fish populations. Unfortunately, little is known about the influence of this sediment on the respiratory performance and feeding abilities of fishes in New Zealand waterways. We examined the effects of suspended sediment (SS) concentrations previously observed after a large‐scale macrophyte removal operation on oxygen consumption (MO 2 ) and feeding rates of brown trout ( Salmo trutta ). MO 2 at 0 mg L −1 , 150 mg L −1 , 300 mg L −1 , 450 mg L −1 and 600 mg L −1 of SS was measured using semi‐closed respirometry. Feeding rates at the same SS concentrations were also measured using laboratory tank experiments. Results suggest that SS concentrations up to 600 mg L −1 have no effect on MO 2 . Conversely, feeding rates were significantly reduced at 450 mg L −1 (22% reduction) and 600 mg L −1 (31% reduction), indicating that sediment concentrations above 450 mg L −1 may negatively affect brown trout populations.